2022
DOI: 10.34172/ddj.2023.408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Anesthesia on the Plasma Glucose Level During Cataract Surgery Among Patients With Type II Diabetes

Abstract: Background: High blood sugar is a typical reaction to stress. In the diabetic population, hyperglycemia can be a serious issue and has been linked to higher mortality rates. Recent studies have shown that anesthetics reduced glucose tolerance; however, it is still unclear how propofol, ketamine, and thiopental of Na affect glucose metabolism. The present study compared the blood glucose levels of thiopental of Na, ketamine, and propofol among patients with cataract surgery. Materials and Methods: The study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Systolic arterial pressure (SAP), diastolic arterial pressure (DAP), left ventricular end-diastolic pressure (LVEDP), the maximum positive change in left ventricular pressure (+ dP/dt max, an index of contractility) and the maximum rate of reduction in left ventricular pressure (− dP/dt max, an index of relaxation velocity) were measured and calculated 42 . In addition, it has been shown that the administration of sodium thiopental did not alter the glucose levels of plasma 43 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Systolic arterial pressure (SAP), diastolic arterial pressure (DAP), left ventricular end-diastolic pressure (LVEDP), the maximum positive change in left ventricular pressure (+ dP/dt max, an index of contractility) and the maximum rate of reduction in left ventricular pressure (− dP/dt max, an index of relaxation velocity) were measured and calculated 42 . In addition, it has been shown that the administration of sodium thiopental did not alter the glucose levels of plasma 43 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini dapat turut memengaruhi pengaturan glukosa dalam darah. Kemungkinan lainnya yang dapat menyebabkan adanya peningkatan glukosa darah pascaoperasi yaitu penggunaan obat-obatan atau anestesi pada proses operasi, yang dapat menyebabkan peningkatan sementara dalam kadar glukosa darah sebagai efek sampingnya (Nasrollahi et al, 2022;Kurihara et al, 2021;Malekki & Soltani, 2018).…”
Section: Analisis Deskriptif Kadar Glukosa Darah Responden Pascaoperasiunclassified